2010
DOI: 10.1111/j.1399-0012.2009.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile‐associated disease in allogeneic hematopoietic stem‐cell transplant recipients: risk associations, protective associations, and outcomes

Abstract: The purpose of this study was to evaluate risk factors, protective factors, and outcomes associated with Clostridium difficile-associated disease (CDAD) in allogeneic hematopoietic stem cell transplant (HSCT) recipients. A case-control study was performed with 37 CDAD cases and 67 controls. In the multivariable logistic regression analysis, receipt of a 3 rd or 4 th generation cephalosporin was associated with increased risk of CDAD (OR=4.6, 95% CI 1.6 -13.1). Receipt of growth factors was associated with decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 19 publications
8
75
5
Order By: Relevance
“…Stevens et al 19 showed that cumulative increase in number of antibiotic doses and duration increased the risk of CDI exponentially. Third-and fourth-generation cephalosporins and ciprofloxacin are the most common antibiotics associated with increased risk of recurrent CDI, 6,20 and we found a similar trend with exception that penicillins were more commonly used. Hensgens et al 20 showed that risk of colonization with C. diff was high during and after 3 months of stopping antibiotic therapy.…”
Section: Discussionsupporting
confidence: 69%
“…Stevens et al 19 showed that cumulative increase in number of antibiotic doses and duration increased the risk of CDI exponentially. Third-and fourth-generation cephalosporins and ciprofloxacin are the most common antibiotics associated with increased risk of recurrent CDI, 6,20 and we found a similar trend with exception that penicillins were more commonly used. Hensgens et al 20 showed that risk of colonization with C. diff was high during and after 3 months of stopping antibiotic therapy.…”
Section: Discussionsupporting
confidence: 69%
“…In most studies, there do not appear to be any unique risk factors among HSCT recipients that are not shared by other nontransplant at-risk patients (256,263). However, in a large study by Dubberke et al, patients who received a third-or fourth-generation cephalosporin were more at risk for development of C. difficile disease (264). This study also demonstrated that the receipt of growth factors was associated with decreased risk (264).…”
Section: Hematopoietic Stem Cell Transplant Patientssupporting
confidence: 48%
“…However, in a large study by Dubberke et al, patients who received a third-or fourth-generation cephalosporin were more at risk for development of C. difficile disease (264). This study also demonstrated that the receipt of growth factors was associated with decreased risk (264). These findings, especially the potentially protective effect of growth factors, need to be verified by prospective studies.…”
Section: Hematopoietic Stem Cell Transplant Patientsmentioning
confidence: 67%
See 1 more Smart Citation
“…Although the exact relationship between GVHD and CDI remains unknown, they may be interrelated, as studies have shown an increased risk for gut and severe GVHD after CDI (Chakrabarti et al, 2000;Dubberke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%